The MENA Region – An Optimal Currency Area? Evaluating its Stability by Taylor-Rule Derived Stress Tests - Karara, Mouchera (Journal of Reviews on Global Economics, 2014)
The European currency union with the EURO as its common currency is the most persistent and largest monetary union to date. At the beginning, it has attracted a lot of attention to the concept of monetary unions; yet, it has recently signaled a lot of warnings around the concept that requires careful studying prior to any duplication attempt. This paper aims at identifying potential currency unions in the MENA region based on interest rates' similarity as one of the aspects that affect a monetary union's success. To assess their sustainability, the optimal interest rates (Taylor rates) of the members of each potential union is estimated and used to calculate a stress level index. The sample used in this study consists of eleven countries where Taylor rates were calculated using data from 1998 to 2008. The stress test results provide a clear result: Two monetary sub-unions, namely the Saudi Arabia - Kuwait union and the Mashreq union (Jordan, Egypt and Syria), are found to have relatively low stress levels and high benefits from a common currency. In contrast, a large MENA union would suffer from very high stress levels and only modest advantages of a common currency.